Crystal structure of a family VIII β‐lactamase fold hydrolase reveals the molecular mechanism for its broad substrate scope. (27th June 2022) - Cea‐Rama, Isabel; Coscolín, Cristina; Gonzalez‐Alfonso, Jose L.; Raj, Jog; Vasiljević, Marko; Plou, Francisco J.; Ferrer, Manuel; Sanz‐Aparicio, Julia
Abstract : Family VIII esterases present similarities to class C β‐lactamases, which show nucleophilic serines located at the S‐X‐X‐K motif instead of the G‐X‐S‐X‐G or G‐D‐S‐(L) motif shown by other carboxylesterase families. Here, we report the crystal structure of a novel family VIII (subfamily VIII. I) esterase (EH7 ; denaturing temperature, 52.6 ± 0.3 °C; pH optimum 7.0–9.0) to deepen its broad substrate range. Indeed, the analysis of the substrate specificity revealed its capacity to hydrolyse nitrocefin as a model chromogenic cephalosporin substrate (40.4 ± 11.4 units·g −1 ), and a large battery of 66 structurally different esters (up to 1730 min −1 ), including bis(2‐hydroxyethyl)‐terephthalate (241.7 ± 8.5 units·g −1 ) and the mycotoxin T‐2 (1220 ± 52 units·g −1 ). It also showed acyltransferase activity through the synthesis of benzyl 3‐oxobutanoate (40.4 ± 11.4 units·g −1 ) from benzyl alcohol and vinyl acetoacetate. Such a broad substrate scope is rare among family VIII esterases and lipolytic enzymes. Structural analyses of free and substrate‐bound forms of this homooctamer esterase suggest that EH7 presents a more opened and exposed S1 site having no steric hindrance for the entrance of substrates to the active site, more flexible R1, R2 and R3 regions allowing for the binding of a wide spectrum of substrates into the active site, and small residues in the conserved motif Y‐X‐X containing the catalytic Tyr enabling the entrance of large substrates. These unique structural elements in combination with docking experiments allowed us to gain valuable insights into the substrate specificity of this esterase and possible others belonging to family VIII. Abstract : We present a comprehensive biochemical and structural study of a family VIII ester hydrolase with a broad and unusual substrate profile, including acyltransferase activities. A wide catalytic cavity accepts an ample set of different esters, some being relevant to plastic and mycotoxin degradation. Depiction of detailed interaction with substrates unravels the plasticity of binding modes and provides valuable insights into the substrate specificity of this esterase and others within family VIII.